Hubungan Tingkat Pemahaman Pasal 28 UUD 1945 terhadap Kebebasan Berbicara dengan Etika - Hendra Mawan; Hermi Yanzi; Berchah Pitoewas (FKIP Unila, 2018)
This study aims to explain the Correlation between the level of understanding of article 28 of the 1945 constitution towards freedom of speech with ethics of communicating on students of grade XI Senior High School 1 Kalianda South Lampung. The method used in this study is a quantitative method. Based on the results of correlational testing, it can be concluded that there is a significant correlation between understanding Article 28 of the 1945 Constitution towards freedom of speech with ethics of communicating on students. It means that there is a correlation between the level of understanding of article 28 of the 1945 Constitution towards freedom of speech with ethics of communicating on students of grade XI of SHS 1 Kalianda, South Lampung. Students who do not understand freedom of speech are those who have less skills in communication with ethics, and students who have a good understanding of freedom of speech are good at communicating with ethics.Penelitian ini bertujuan untuk menjelaskan hubungan tingkat pemahaman pasal 28 UUD 1945 terhadap kebebasan berbicara dengan etika berkomunkasi peserta didik kelas XI SMA Negeri 1 Kalianda Lampung Selatan. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif. Berdasarkan hasil pengujian hubungan, menunjukan adanya hubungan yang signifikan antara pemahaman pasal 28 UUD 1945 terhadap kebebasan berbicara dengan etika berkomunikasi peserta didik. Artinya, ada hubungan tingkat pemahaman pasal 28 UUD 1945 Terhadap kebebasan berbicara dengan etika berkomunikasi peserta didik kelas XI SMA Negeri 1 Kalianda Lampung Selatan. Jika peserta didik yang kurang paham akan kebebasan berbicara maka peserta didik itu juga kurang baik dalam etika berkomunikasi sebaliknya jika peserta didik tersebut sudah paham akan kebebasan berbicara maka peserta didik tersebut baik dalam etika berkomunikasi. Kata kunci : Kebebasan Berbicara, komunikasi, Pasal 28 UUD 1945